Effects of staggered truncated ribs on thermal-hydraulic performance and entropy generation of microchannel heat sinks - Dongkai Wang; Lirui Xue; Chang Liu; Haitao Chen; Changquan Xia; Qinyu Qian; Liwen Cheng (Case Studies in Thermal Engineering)
A microchannel with staggered truncated ribs (MC-STR) is presented. The effects of rib height ratio (α) and rib width ratio (β) on the thermal-hydraulic performance and entropy generation are investigated by numerical simulation at the Reynolds numbers (Re) range of 223–593. Initially, to compare the MC-STR of different α configurations, the traditional ribbed microchannel (MC-TR) and the smooth microchannel (MC-S) are also numerically analyzed. Subsequent analysis further investigates the effect of β on convective heat transfer in MC-STR. The results indicate that MC-STR significantly enhances the heat transfer and reduces the heated wall temperature. Increasing α and β results in higher Nusselt number (Nu) and friction coefficient (f). Compared to MC-TR, MC-STR effectively reduces pressure drop losses and exhibits higher Nu at α = 0.75 and α = 0.5 for most Re. Overall, the highest comprehensive thermal performance factor (PEC) of 1.355 for MC-STR (α = 0.5, β = 0.3) is attained at Re = 593. Furthermore, the augmentation entropy generation number (Ns,a) of MC-STR (α = 0.75, β = 0.3) reaches the lowest value of 0.422 for Re = 593.